Risk Factors for Breast Cancer in the Female Population - Yoenny Peña García; Maikel Maceo González; Diamela Ávila Céspedes; Licet Utria Velázquez; Yohandra Más López (Revista Finlay)
Introduction: breast cancer is the excessive growth of malignant cells in the breast tissue. In Cuba, this condition is the first cause of incidence and mortality among female sex malignant neoplasms. Objective: to determine the risk factors strength of association for breast cancer in the female population at Delicias health area, from 2011 to 2015. Method: a case and control epidemiological study was carried out. A sample was taken by the simple random method, which was made up of 75 people (25 cases and 50 controls). The variables analyzed were: family history of breast cancer, late menopause, hormonal treatment, nulliparity, smoking, births in advanced age, precocious menarche, alcoholism, obesity, non-breastfeeding, and inadequate diet. Chi2, Odd Ratio (OR) and Pearson's linear correlation coefficient were calculated, the absolute risk and it was stratified by communities. Multiple logistic regression was applied. Results: the greatest association strength risk factors were: births in advance age, smoking, hormone replacement therapy and late menopause. Conclusions: it was demonstrated that risk factors for breast cancer which affect the territory in order of importance are: family history of breast cancer, late menopause, hormonal treatment, nulliparity, smoking, deliveries in advanced age, early menarche, alcoholism, obesity, non-breastfeeding, and inadequate diet.